A key role of the mitochondrial citrate carrier (SLC25A1) in TNFα- and IFNγ-triggered inflammation - Infantino, Vittoria (Biochim Biophys Acta, 2014)
The chronic induction of inflammation underlies multiple pathological conditions, including metabolic, autoimmune disorders and cancer. The mitochondrial citrate carrier (CIC), encoded by the SLC25A1 gene, promotes the export of citrate from the mitochondria to the cytoplasm, a process that profoundly influences energy balance in the cells. We have previously shown that SLC25A1 is a target gene for lipopolysaccharide signaling and promotes the production of inflammatory mediators. We now demonstrate that SLC25A1 is induced at the transcriptional level by two key pro-inflammatory cytokines, tumor necrosis factor-α (TNFα) and interferon-γ (IFNγ), and such induction involves the activity of the nuclear factor kappa B and STAT1 transcription factors. By studying the down-stream events following SLC25A1 activation during signals that mimic inflammation, we demonstrate that CIC is required for regulating the levels of nitric oxide and of prostaglandins by TNFα or IFNγ. Importantly, we show that the citrate exported from mitochondria via CIC and its downstream metabolic intermediate, acetyl-coenzyme A, are necessary for TNFα or IFNγ to induce nitric oxide and prostaglandin production. These findings provide the first line of evidence that the citrate export pathway, via CIC, is central for cytokine-induced inflammatory signals and shed new light on the relationship between energy metabolism and inflammation.